Cardiac Myocyte Dysfunction Induced by Streptolysin O Is Membrane Pore and Calcium Dependent. Issue 2 (February 2015) - Bolz, Devin D.; Li, Zhi; McIndoo, Eric R.; Tweten, Rodney K.; Bryant, Amy E.; Stevens, Dennis L.
Abstract : ABSTRACT: Septic cardiomyopathy is a severe complication among some patients who develop group A streptococcal toxic shock syndrome. Despite the importance of cardiac dysfunction in determining prognosis, very little is known about mechanisms that reduce cardiac output in association with streptococcal infection. Here, we investigated the effects of streptococcal extracellular toxins on mechanical contractility of electrically paced primary murine cardiomyocytes. Our data demonstrate that streptolysin O (SLO) is the major streptococcal toxin responsible for cardiomyocyte contractile dysfunction. Streptolysin O dose-dependently affected cardiac myocyte function in discrete stages. Exposure to SLO caused a failure of cardiac cells to respond to electrical pacing, followed by spontaneous dysregulated contractions and augmented strength of contraction. Central to these SLO-mediated effects is a marked influx of calcium into the cytosol through SLO-mediated pores in the cytoplasmic membrane. Such calcium mobilization in response to SLO correlated temporally with hypercontractility and unpaced contractions. During continued exposure to SLO, cardiomyocytes exhibited periods of reversion to normal electrical pacing suggestive of membrane lesion repair and restoration of calcium handling. Together, these observations are consistent with the clinical observation that septic cardiomyopathy is a reversible condition in patients who survive streptococcal toxic shock syndrome. These data provide strong evidence that streptococcal exotoxins, specifically SLO, can directly impact cardiac mechanical function.